Flexible sulfide solid electrolyte and all-solid-state battery including same
By adjusting the ratio of bromine to chlorine and controlling the type and content of polymer binder, a high-flexible sulfide phosphate solid electrolyte layer was prepared, which solved the problem of insufficient mechanical flexibility of the electrolyte layer in the prior art and improved the safety and reliability of the battery.
Patent Information
- Application Number
- JP2024547197
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2023-07-12
- Publication Date
- 2025-04-16
AI Technical Summary
In the prior art, the solid electrolyte layer of sulfide phosphate lacks sufficient mechanical flexibility and is prone to rupture or cracks during the treatment process, resulting in electronic contact between the positive and negative electrodes, causing safety hazards such as heat release and fire.
By adjusting the ratio of bromine (Br) and chlorine (Cl), controlling the type and content of polymer binder, a high flexibility of sulfide solid electrolyte layer was prepared. The electrolyte layer still maintains a small bending radius and a high bending strain under high strain, reducing the occurrence of cracks and wrinkles.
The high flexibility characteristics of the solid electrolyte layer of sulfide phosphate is achieved, reducing the risk of cracking and cracking of the electrolyte layer during the treatment process, and improving the safety and reliability of the battery.
Smart Images

Figure 2025511438000001_ABST
Abstract
Description
Priority
[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 390699, filed July 20, 2022, the entire contents of which are incorporated herein by reference in their entirety. [Technical field]
[0002] The present disclosure relates to flexible sulfide solid electrolytes for all-solid-state batteries. [Background technology]
[0003] All-solid-state batteries (ASSBs) have attracted attention due to their potential for safety and higher energy density than conventional lithium-ion batteries based on organic liquid electrolytes. Among them, ASSBs with thiophosphate-based solid electrolytes (SEs) are promising due to their high ionic conductivity and good mechanical compatibility. As an alternative to conventional liquid electrolytes, the SE layer is sandwiched between the positive and negative electrodes. In addition, the SE layer serves the functions of both electrolyte and separator, which allows the transport or flow of ions and prevents electronic contact between the positive and negative electrodes.
[0004] General requirements for the solid electrolyte (SE) layer include a) good ionic conductivity, b) good chemical / electrochemical stability against oxidation or reduction from the original state, and c) physical / mechanical strength to prevent direct or electronic contact between the positive and negative electrodes (which would normally result in catastrophic heat dissipation and fire or explosion).
[0005] So far, there has been no or little research on the physical properties of thiophosphate SE layers. Mechanical flexibility is an important physical property of thiophosphate SE layers. SE layers can be broken or cracked during handling processes. Defects and / or cracks can result in electronic contact between the positive and negative electrodes.
[0006] The present disclosure provides a flexible thiophosphate SE layer that is less likely to crack and wrinkle even under high strain.
[0007] Patent Document 1 discloses a flexible composite membrane including a polymeric porous support whose pores are filled with an inorganic solid electrolyte. The flexibility of this composite membrane is due to the flexible polymeric support. However, the use of polymers would have the disadvantages of low ionic conductivity, low thermal stability, and insufficient safety due to flammability.
[0008] Patent Document 2 discloses a stretchable and flexible lithium-ion battery containing a polymer-based flexible electrolyte, the electrolyte being selected from sodium (Na) superionic conductors (NASICON), garnets, perovskites, lithium (Li) superionic conductors (LISICON), lithium oxynitride phosphate (LiPON), Li3N, argyrodite-type sulfides, and antiperovskites. The document also discloses that the polymer-based thin electrolyte is suitable for obtaining an electrolyte with high ionic conductivity that is conformable and flexible. The document does not provide any flexible inorganic electrolyte.
[0009] Eckert, Zhang and Kennedy performed thermomechanical optimization experiments on the Li2P-P2S5 system and showed that, overall, the samples did not have a single phase (Non-Patent Document 1). Patent Document 3 discloses a single-phase lithium argyrodite. However, the document does not disclose any mechanical properties or any method for preparing a soft SE. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] U.S. Patent No. 11024876B2 [Patent Document 2] International Publication No. 2021 / 016319A1 [Patent Document 3] U.S. Patent No. 8,075,865 B2 [Non-patent literature]
[0011] [Non-Patent Document 1] Chem. of Mat. 1990, 2, 273-279 Summary of the Invention [Problem to be solved by the invention]
[0012] There is a need for flexible SEs and solid-state batteries comprising same. [Means for solving the problem]
[0013] The present disclosure provides a flexible solid electrolyte layer based on an argyrodite-type lithium ion conducting material. In one embodiment, the flexibility of the argyrodite-type SE layer is achieved by adjusting the ratio of bromine (Br) to chlorine (Cl). In another embodiment, the flexibility of the argyrodite-type SE layer is achieved by adjusting 1) the Br / Cl ratio, 2) the type of polymer binder, and / or 3) the content of the binder in a mixture such as a slurry.
[0014] The present disclosure provides a flexible membrane of a sulfide solid electrolyte. In one embodiment, the sulfide solid electrolyte is argyrodite. In one embodiment, the flexible membrane has a bend radius of 4 cm or less. In one embodiment, the flexible membrane has a bend strain of 0.1% or more.
[0015] Definitions and Abbreviations The following terms shall be used to describe this disclosure. Unless a specific definition is provided herein, the terms used to describe this disclosure shall be given their ordinary meanings as understood by one of ordinary skill in the art.
[0016] As used herein, "bend radius" is a parameter that characterizes the flexibility of a material and is typically measured at the radius that corresponds to a bent or curved sheet or film specimen when bent without observable damage (Kim T, et al., "Bending Strain and Bending Fatigue Lifetime of Flexible Metal Electrodes on Polymer Substrates," Materials 2019, 12, 2490). Observable damage may include cracks, crimps, or wrinkles. In one embodiment, the sheet or film has a thickness of 10 to 200 μm. In one embodiment, the sheet or film has a width or length of 3.0 to 10 cm. In one embodiment, the sheet or film is a 5.4 cm x 5.4 cm square sheet with a thickness of 90 μm. In one embodiment, bending strain may also be used to measure the bendability or flexibility of a layer or film. In one embodiment, bending strain (ε M ) is typically calculated with the commonly used single layer model and is given by the following equation (Kim T, et al., “Bending Strain and Bending Fatigue Lifetime of Flexible Metal Electrodes on Polymer Substrates,” Materials 2019, 12, 2490): ε M =h / (2r) where h is the thickness of the sample and r is the minimum bending radius without damage (e.g., cracking, wrinkling, or crimping). M A higher value of indicates better flexibility. [Brief description of the drawings]
[0017] [Figure 1A] Figure 1 shows a typical measurement of the bending radius using a solid electrolyte membrane with dimensions of 5.4 cm x 5.4 cm and a thickness of 90 μm. [Figure 1B]Figure 1 shows a typical measurement of the bending radius using a solid electrolyte membrane with dimensions of 5.4 cm x 5.4 cm and a thickness of 90 μm. [Figure 1C] Figure 1 shows a typical measurement of the bending radius using a solid electrolyte membrane with dimensions of 5.4 cm x 5.4 cm and a thickness of 90 μm. [Figure 1D] Figure 1 shows a typical measurement of the bending radius using a solid electrolyte membrane with dimensions of 5.4 cm x 5.4 cm and a thickness of 90 μm. [Figure 2A] Graph showing a typical relationship between Br / Cl ratio and bend radius for a compound having the formula Li5.8PS4.8ClaBrb, where a+b=1.2. [Figure 2B] Graph showing a typical relationship between Br / Cl ratio and bend radius for a compound having the formula Li5.4PS4.4ClaBrb, where a+b=1.6. [Diagram 3] X-ray diffraction (XRD) patterns of Examples 2, 4, 8 and Comparative Examples 1 and 2 [Figure 4] Graph showing flexible SEs prepared with two typical binders at different Br / Cl ratios DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] In one embodiment, the present disclosure provides a compound having the formula I and an argyrodite-type crystal structure: Li x M1 y M2 z P 1-p M3 p S 6-a-b-q O q Cl a Br bA flexible electrolyte membrane of a sulfide solid electrolyte comprising a compound having an argyrodite-type crystal structure, which is represented by the formula (I): wherein 4 ≤ x ≤ 8, 0 ≤ y < 1, 0 ≤ z < 1, 0 ≤ p < 1, 0 ≤ q < 1, 0 < a ≤ 2, 0 ≤ b < 2, 0 < 6 - a - b - q < 6, 0 < 1 - p ≤ 1, 0 ≤ b / a ≤ 3.5, M1 is at least one element of Group 1 or Group 11 other than H or Li in the periodic table, M2 is at least one element of Group 2 in the periodic table, and M3 is at least one element of Group 14 in the periodic table.
[0019] In one embodiment, the flexible electrolyte membrane disclosed in the present disclosure has a cubic crystal structure. In one embodiment, the electrolyte is confirmed by XRD TIFF2025511438000002.tif5114
[0020] to have a crystal structure within the space group.
[0021] In one aspect, the present disclosure provides a formula: Li x M1 y M2 z P 1-p M3 p S 6-a-b-q O q Cl a Br b A flexible electrolyte membrane of a sulfide solid electrolyte having the formula (I): wherein 4 ≤ x ≤ 8, 0 ≤ y < 1, 0 ≤ z < 1, 0 ≤ p < 1, 0 ≤ q < 1, 0 < a ≤ 2, 0 ≤ b < 2, 0 < 6 - a - b - q < 6, 0 < 1 - p ≤ 1, 0 ≤ b / a ≤ 7, M1 is at least one element of Group 1 or Group 11 other than H or Li in the periodic table, M2 is at least one element of Group 2 in the periodic table, and M3 is at least one element of Group 14 in the periodic table.
[0022] In one embodiment, the flexible electrolyte membrane has a bending strain (ε M ) of 0.1% or more, and the bending strain is represented by the formula: ε M = h / (2r) where h is the thickness of the membrane and r is the bend radius achieved without damage to the membrane (e.g., cracks, wrinkles, or crimps).
[0023] In one embodiment, the flexible electrolyte membrane has a thickness in the range of 5 μm to 300 μm, 10 μm to 300 μm, 20 μm to 300 μm, 50 μm to 300 μm, 2 μm to 500 μm, 5 μm to 500 μm, 10 μm to 500 μm, 10 μm to 500 μm, 20 μm to 500 μm, 50 μm to 500 μm, or any and all ranges and sub-ranges therebetween.
[0024] In some embodiments, the electrolyte membrane has a lithium ion conductivity of 0.02 mS / cm or more, 0.05 mS / cm or more, 0.1 mS / cm or more, 0.2 mS / cm or more, 0.5 mS / cm or more, or 1 mS / cm or more. In some embodiments, the flexible electrolyte membrane has a lithium ion conductivity of 0.05 mS / cm to 10 mS / cm, 0.1 mS / cm to 10 mS / cm, 0.25 mS / cm to 10 mS / cm, 0.5 mS / cm to 10 mS / cm, 0.75 mS / cm to 10 mS / cm, 0.05 mS / cm to 20 mS / cm, 0.1 mS / cm to 20 mS / cm, 0.25 mS / cm to 20 mS / cm, The lithium ion conductivity ranges from 0.5 mS / cm to 20 mS / cm, from 0.75 mS / cm to 20 mS / cm, from 0.05 mS / cm to 50 mS / cm, from 0.1 mS / cm to 50 mS / cm, from 0.25 mS / cm to 50 mS / cm, from 0.5 mS / cm to 50 mS / cm, from 0.75 mS / cm to 50 mS / cm, or any and all ranges and sub-ranges therebetween.
[0025] In some embodiments, the electrolyte membrane has a bending strain of 0.1% or more and a lithium ion conductivity of 0.02 mS / cm or more. In some embodiments, the electrolyte membrane has a bending strain of 0.1% or more and a lithium ion conductivity of 0.05 mS / cm or more. In some embodiments, the electrolyte membrane has a bending strain of 0.1% or more and a lithium ion conductivity of 0.1 mS / cm or more. In some embodiments, the electrolyte membrane has a bending strain of 0.1% or more and a lithium ion conductivity of 0.2 mS / cm or more. In some embodiments, the electrolyte membrane has a bending strain of 0.1% or more and a lithium ion conductivity of 0.5 mS / cm or more. In some embodiments, the electrolyte membrane has a bending strain of 0.1% or more and a lithium ion conductivity of 0.55 mS / cm or more. In some embodiments, the electrolyte membrane has a bending strain of 0.1% or more and a lithium ion conductivity of 0.60 mS / cm or more. In some embodiments, the electrolyte membrane has a bending strain of 0.1% or more and a lithium ion conductivity of 0.65 mS / cm or more. In some embodiments, the electrolyte membrane has a bending strain of 0.1% or greater and a lithium ion conductivity of 0.7 mS / cm or greater.
[0026] In one embodiment, the formula of the sulfide electrolyte includes at least one element selected from the group consisting of M1, M2, M3, and O. In some embodiments, formula (I) contains one element selected from the group consisting of M1, M2, M3, and O. In some embodiments, formula I is: 1) Li x P.S. 6-a-b-q O q Cl a Br b , where 4≦x≦8, 0 <q≦1、0<a≦2、0≦b<2、0<6-a-b-q<6; 2) Li x M1 y P.S. 6-a-b Cl a Br b , where 4≦x≦8, 0 <y<1、0<a≦2、0≦b<2、0<6-a-b<6; 3) Li x M2 z P.S. 6-a-b Cl a Br b , where 4≦x≦8, 0 <z≦1、0<a≦2、0≦b<2、0<6-a-b<6;および 4) Li x P 1-p M3 p S 6-a-b Cl a Br b , where 4≦x≦8, 0 <p≦1、0<a≦2、0≦b<2、0<6-a-b<6、0<1-p≦1; is selected from the group consisting of:
[0027] In some embodiments, the molar amount of Br in the formula has a value greater than zero, ie, b>0.
[0028] In some embodiments, M1 is at least one element from group 1 or group 11 of the periodic table other than H or Li. In some embodiments, M1 is at least one selected from the group consisting of Na, K, Rb, Cs, Cu, Ag, and Au. In some embodiments, M1 is selected from the group consisting of Na, Cu, and Ag. In some embodiments, M2 is at least one element from group 2 of the periodic table. In some embodiments, M2 is at least one selected from the group consisting of Be, Mg, Ca, Sr, and Ba. In some embodiments, M3 is at least one element from group 14 of the periodic table. In some embodiments, M3 is at least one selected from the group consisting of Si, Ge, Sn, and Pb.
[0029] Incorporating oxygen into the formula makes such materials more stable and / or less sensitive to oxygen and water. In one embodiment, the formula is: x P.S. 6-a-b-q O q Cl a Br bwhere 4 ≦ x ≦ 8, 0 < q ≦ 1, 0 < a ≦ 2, 0 ≦ b < 2, and 0 < 6 - a - b - q < 6, the molar amount of O is determined by q having values in the range from 0 to 0.1, from 0 to 0.2, from 0 to 0.3, from 0 to 0.4, from 0 to 0.5, from 0 to 0.6, from 0.001 to 0.1, from 0.001 to 0.2, from 0.001 to 0.3, from 0.001 to 0.4, from 0.001 to 0.5, from 0.001 to 0.6, from 0.002 to 0.1, from 0.002 to 0.2, from 0.002 to 0.3, from 0.002 to 0.4, from 0.002 to 0.5, from 0.002 to 0.6, from 0.005 to 0.1, from 0.005 to 0.2, from 0.005 to 0.3, from 0.005 to 0.4, from 0.005 to 0.5, from 0.005 to 0.6, or any and all ranges and sub - ranges therebetween. In one embodiment, the formula is Li 5.8 PS 4.7 O 0.1 Cl 1.2 In one embodiment, the formula is Li x PS 6-a-b-q O q Cl a Br b where 4 ≦ x ≦ 8, 0 < q ≦ 1, 0 < a ≦ 2, 0 < b < 2, and 0 < 6 - a - b - q < 6. In some embodiments, b / a has values in the range from 0 to 3.5. In some embodiments, b / a has values in the range from 0 to 7. In some embodiments, b / a has values in the range from 0 to 10, from 0 to 15, or from 0 to 20. In some embodiments, b / a has values greater than zero.
[0030] In one embodiment, when the formula is Li x M1 y PS 6-a-b Cl a Br bwhere 4 ≦ x ≦ 8, 0 < y < 1, 0 < a ≦ 2, 0 ≦ b < 2, and 0 < 6 - a - b < 6, b / a has a value in the range from 0 to 3.5. In some embodiments, b / a has a value in the range from 0 to 7. In some embodiments, b / a has a value in the range from 0 to 10, from 0 to 15, or from 0 to 20. In some embodiments, b / a has a value greater than zero.
[0031] In one embodiment, the formula is Li x M2 z PS 6-a-b Cl a Br b where 4 ≦ x ≦ 8, 0 < z ≦ 1, 0 < a ≦ 2, 0 ≦ b < 2, and 0 < 6 - a - b < 6, b / a has a value in the range from 0 to 3.5. In some embodiments, b / a has a value in the range from 0 to 7. In some embodiments, b / a has a value in the range from 0 to 10, from 0 to 15, or from 0 to 20. In some embodiments, b / a has a value greater than zero.
[0032] In one embodiment, the formula is Li x P 1-p M3 p S 6-a-b Cl a Br b where 4 ≦ x ≦ 8, 0 < p ≦ 1, 0 < a ≦ 2, 0 ≦ b < 2, 0 < 6 - a - b < 6, and 0 < 1 - p ≦ 1, b / a has a value in the range from 0 to 3.5. In some embodiments, b / a has a value in the range from 0 to 7. In some embodiments, b / a has a value in the range from 0 to 10, from 0 to 15, or from 0 to 20. In some embodiments, b / a has a value greater than zero.
[0033] In some embodiments, formula (I) includes O and one element selected from the group consisting of M1, M2, and M3. In some embodiments, the sulfide solid electrolyte is Li x M1 y PS 6-a-b-q O qCl a Br b (4 ≤ x ≤ 8, 0 < y < 1, 0 < q < 1, 0 < a ≤ 2, 0 ≤ b < 2, 0 < 6 - a - b - q < 6), Li x M2 z PS 6-a-b-q O q Cl a Br b (4 ≤ x ≤ 8, 0 < z < 1, 0 ≤ q < 1, 0 < a ≤ 2, 0 ≤ b < 2, 0 < 6 - a - b - q < 6), and Li x P 1-p M3 p S 6-a-b-q O q Cl a Br b (4 ≤ x ≤ 8, 0 < p < 1, 0 < q < 1, 0 < a ≤ 2, 0 ≤ b < 2, 0 < 6 - a - b - q < 6, 0 < 1 - p < 1) having a formula selected from the group consisting of. In one embodiment, formula (I) does not contain M1, M2, or M3 and contains O. In one embodiment, the formula of the sulfide electrolyte is Li x PS 6-a-b-q O q Cl a Br b (4 ≤ x ≤ 8, 0 < q < 1, 0 < a ≤ 2, 0 ≤ b < 2, 0 < 6 - a - b - q < 6). In some embodiments, the molar amount of Br in the formula has a value greater than zero, i.e., b > 0.
[0034] In one embodiment, the total molar amount of halogen in the formula of the sulfide electrolyte is 2 or less, i.e., a + b ≤ 2. In one embodiment, the total molar amount of halogen in the formula is 2 or more and 3 or less, i.e., 2 ≤ a + b ≤ 3. In one embodiment, the total molar amount of halogen in the formula is 2 or more and less than 4, i.e., 2 ≤ a + b < 4. In one embodiment, the total molar amount of Br and Cl in the formula is 2 or less, i.e., a + b ≤ 2. In one embodiment, the total molar amount of Br and Cl in the formula is 2 or more and 3 or less, i.e., 2 ≤ a + b ≤ 3. In one embodiment, the total molar amount of Br and Cl in the formula is 2 or more and less than 4, i.e., 2 ≤ a + b < 4.
[0035] In one embodiment, the sulfide solid electrolyte is Li 5.8 P.S. 4.7 O 0.1 Cl 1.2 , Li 5.9 P 0.9 Ge 0.1 S 4.8 Cl 1.2 , Li 5.7 Na 0.1 P.S. 4.8 Cl 1.2 , Li 5.4 P.S. 4.4 Cl 0.4 Br 1.2 , Li 5.8 P.S. 4.8 Cl 0.4 Br 0.8 , Li 5.4 P.S. 4.4 Cl 0.6 Br 1.0 , Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 , Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 , Li 5.8 P.S. 4.8 Cl 0.6 Br 0.6 , Li 5.4 P.S. 4.4 Cl 1.0 Br 0.6 , Li 5.4 P.S. 4.4 Cl 1.2 Br 0.4 , Li 5.8 P.S. 4.8 Cl 0.8 Br 0.4 , Li 5.8 P.S. 4.8 Cl 1.0 Br 0.2 , and Li 5.4 P.S. 4.4 Cl 1.4 Br 0.2 The compound has a formula selected from the group consisting of:
[0036] In some embodiments, the flexible SE membrane comprises 0.02% to 5% by weight, 0.02% to 10% by weight, 0.02% to 15% by weight, 0.02% to 20% by weight, 0.05% to 5% by weight, 0.05% to 10% by weight, 0.05% to 15% by weight, 0.05% to 20% by weight, 0.1% to 5% by weight, 0.1% to 10% by weight, 0.1% to 15% by weight, 0.1% to 20% by weight %, 0.2% to 5%, 0.2% to 10%, 0.2% to 15%, 0.2% to 20%, 0.5% to 5%, 0.5% to 10%, 0.5% to 15%, 0.5% to 20%, 1% to 5%, 1% to 10%, 1% to 15%, 1% to 20%, or any ranges and sub-ranges therebetween.
[0037] In one embodiment, the present disclosure provides an all-solid-state battery comprising the flexible electrolyte membrane disclosed herein.
[0038] In one embodiment, the all-solid-state battery further comprises a positive electrode made from a positive electrode electroactive material.
[0039] In one embodiment, the positive electrode electroactive material exhibits redox reactions at a potential of 2 V or greater versus a lithium electrode during operation of the all-solid-state battery.
[0040] In one embodiment, the positive electrode electroactive material contains Li, Ni, and Co. In one embodiment, the positive electrode electroactive material contains Li, Ni, and Co, and at least one of Mn and Al.
[0041] In one embodiment, the positive electrode electroactive material contains at least one of Fe and P.
[0042] In one embodiment, the all-solid-state battery further comprises a positive electrode layer containing a positive electrode active material and an anode layer, and a flexible electrolyte membrane is disposed between the positive electrode layer and the anode layer.
[0043] In one embodiment, the negative electrode layer comprises particles of a carbon-based conductive material comprising at least one selected from the group consisting of carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, natural graphite, and artificial graphite.
[0044] In one embodiment, the negative electrode layer comprises a metal comprising at least one selected from the group consisting of lithium, sodium, magnesium, aluminum, silicon, calcium, titanium, manganese, iron, cobalt, nickel, zinc, molybdenum, silver, indium, tin, and tungsten.
[0045] In one embodiment, the flexibility of the electrolyte membrane or layer disclosed herein is not only due to the polymeric porous support layer (underlayer). To exclude the influence of the polymeric porous support layer on flexibility, the same polymeric porous support was used in all the examples in Table 1, so that other factors such as Br / Cl ratio, type of polymeric binder, and content of polymeric binder were investigated.
[0046] In one aspect, the present disclosure provides a method for preparing a flexible electrolyte membrane by a wet method or a dry method. In one embodiment, the wet method comprises: 1) mixing particles of a sulfide electrolyte having formula (I), a binder and a solvent to obtain a slurry; 2) coating the slurry onto a substrate comprising a film and a nonwoven fabric, followed by vacuum drying at room temperature to obtain a dry coating bonded to the nonwoven fabric; and 3) peeling off the dried coating together with the nonwoven fabric from the film, thereby obtaining an electrolyte membrane; It may include:
[0047] In one embodiment, when the slurry is applied to the substrate nonwoven fabric, the pores of the nonwoven fabric are filled with a mixture containing particles, binder and solvent. Once a dry coating is formed after the solvent is substantially removed, the nonwoven fabric is bonded to and forms part of the electrolyte layer.
[0048] In one embodiment, sulfide electrolyte particles are prepared by mixing precursor powders in stoichiometric ratio in an inert atmosphere, followed by sintering at 400-700° C. for 4-24 hours and grinding. In some embodiments, the precursor powders include Li2S, Na2S, P2S5, LiCl, LiBr, Li2O, and GeS2.
[0049] In one embodiment, the wet process binder may be a rubber type binder such as a non-aqueous acrylate type binder, styrene-butadiene rubber (SBR), nitrile butadiene rubber (NBR), poly(vinylidene fluoride) (PVDF), polyethylene (PE), vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride-co-trichloroethylene, polyacrylonitrile, polymethyl methacrylate, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polysaccharide polymers and carboxymethyl cellulose, or a combination thereof.
[0050] In one embodiment, the solvent comprises xylene.
[0051] In one embodiment, the particles, binder, and solvent are mixed in a planetary mixer.
[0052] In one embodiment, the film in the substrate is a PET film. In one embodiment, the nonwoven serves as a backing layer or mechanical support layer. In one embodiment, the nonwoven is made of polyester. Non-limiting examples of polyester include polyethylene terephthalate (PET). In some embodiments, the nonwoven has a thickness of about 7.5 μm, about 10 μm, about 12 μm, about 15 μm, about 17 μm, or about 20 μm. In some embodiments, the nonwoven has a porosity of about 70%, 73%, about 75%, about 78%, or about 80%.
[0053] In some embodiments, the method further comprises stripping the dried coating with the primer layer from the film.
[0054] In another embodiment, an exemplary dry process includes: 1) mixing particles of a sulfide electrolyte having formula (I) with a binder to obtain a mixture; and 2) forming the mixture into an electrolyte membrane; It may include:
[0055] In some embodiments, the binder is a fibrillizable binder. In some embodiments, fibrillizable binders include polytetrafluoroethylene (PTFE), ultra-high molecular weight (UHMW) polyethylene (PE), and combinations thereof. In some embodiments, the particles and binder are mixed at a temperature below the melting point of the binder and sufficient to soften the binder. In some embodiments, the temperature is in the range of 70° C. to 300° C., 80° C. to 300° C., 90° C. to 300° C., 100° C. to 300° C., 110° C. to 300° C., 120° C. to 300° C., 130° C. to 300° C., 150° C. to 300° C., or any and all ranges and sub-ranges therebetween.
[0056] In some embodiments, the mixture is formed into an electrolyte membrane by calendering, hi one embodiment, the calendering is performed with a roller.
[0057] The present disclosure will be better understood with reference to the following experimental details, however, those skilled in the art will readily appreciate that the specific experiments detailed are merely illustrative and are not intended to limit the disclosure as described herein, which disclosure is defined by the claims that follow.
[0058] Please note that the transitional phrase "comprising," which is synonymous with "including," "containing," or "characterized by," is inclusive or open-ended and does not exclude additional, unrecited elements or method steps. EXAMPLES
[0059] Synthesis of solid electrolyte materials Precursor powders were prepared in a stoichiometric ratio in a glove box with an inert Ar atmosphere. Examples of precursor powders include, but are not limited to, Li2S, Na2S, P2S5, LiCl, LiBr, Li2O, GeS2, and any combinations thereof. These powders were ball-milled in a planetary centrifugal mixer for 4 hours. These powders were then sintered at 450 °C for 12 hours.
[0060] Thereby, a solid electrolyte material having an argyrodite-type structure was obtained. After the grinding procedure, the solid electrolyte particles have an average particle size in the range of 1 to 10 μm and will be used for slurry preparation.
[0061] Preparation of solid electrolyte slurry The solid electrolyte, binder, solvent, and zirconia grinding media were mixed using a planetary mixer. The binders include, but are not limited to, PTFE, rubber type binders such as SBR, and non-aqueous acrylate type binders. The solvents include, but are not limited to, xylene.
[0062] Preparation of solid electrolyte membrane The obtained solid electrolyte slurry was coated onto a release polyethylene terephthalate film (50 μm) using a doctor blade in a drying room with a dew point below -50°C, and then the film was dried overnight in a vacuum oven at room temperature. A non-woven fabric was used as an underlayer to provide the necessary mechanical support for the free-standing solid electrolyte layer. The thickness of the produced solid electrolyte layer was about 90 μm. The solid electrolyte layer was cut into a membrane with a size of 5.4 cm x 5.4 cm for testing.
[0063] Characterization and testing of solid electrolyte membranes Powder X-ray diffraction (XRD) measurements were performed using an X-ray diffractometer (SmartLab, Rigaku) by irradiating with Cu-Kα radiation. Diffraction data were collected over 2θ angles from 5 to 60° at a scan rate of 3° / min with a step of 0.05°. XRD measurements were performed using an airtight container to prevent air exposure to the electrolyte powder. For ionic conductivity, the SE membrane was first molded into a disk with a diameter of 1.2 cm and pressed into a torque cell (PEEK) with a stacking pressure of 375 MPa. A titanium plunger was used as a current collector. The ionic conductivity of the solid electrolyte membrane was measured by electrochemical impedance spectroscopy (EIS) and collected in the range of 1 Hz to 7 MHz using a potentiostat (SP200, Biologic) with an applied AC voltage of 10 mV. All measurements were performed at room temperature.
[0064] 1A to 1D provide an exemplary procedure for measuring the bending radius according to one embodiment of the present disclosure. A solid electrolyte membrane with a size of 5.4 cm×5.4 cm and a thickness of 90 μm was first prepared ( FIG. 1A ). A bending force was applied to the membrane to bring two opposite edges closer to each other ( FIG. 1B ). The flexibility of the membrane was reflected by the distance between these two opposite edges during which no wrinkles or cracks were observed in the membrane, or the bending radius (r) corresponding to the bent or curved membrane, as shown in FIG. 1C . Once the membrane was overbent, wrinkles or cracks were observed in the membrane, as shown by the arrows in FIG. 1D . A smaller value of the bending radius suggests a higher flexibility of the membrane. In one embodiment, the bending test is performed with the naked eye or under a microscope or optical magnifier.
[0065] Table 1 shows the bending radius (r) and strain (ε M ), and Li-ion conductivity are summarized.
[0066] Figure 2A shows the Li 5.8 P.S. 4.8 Cl a Br b FIG. 2B shows a typical relationship between Br / Cl ratio and bend radius for an SE sheet or membrane having the formula: 5.4 P.S. 4.4 Cl a Br b Figure 1 shows a typical relationship between Br / Cl ratio and bending radius for an SE sheet or membrane having the formula: where the total mole fraction of halogens, i.e., a+b, is 1.6. Both figures clearly show that when the Br / Cl ratio is 4 or less, the membrane exhibits better flexibility, i.e., bending radius (r) of 4 cm or less and bending strain of 0.1% or more.
[0067] Also as shown in Table 1, the SE may contain other elements including, without limitation, O and Ge. In one embodiment, the SE does not contain Br.
[0068] [Table 1]
[0069] As shown in FIG. 4, flexible SE membranes (with bending strain of at least 0.1%) were obtained. It is clearly shown that increasing the amount of polymer binder will result in a flexible SE membrane. For binder 1, the curve fit is given by the equation: Br / Cl=183x-2.11 (Formula I) where x is the weight percent of binder 1 in the SE membrane.
[0070] Formula I describes the highest Br / Cl ratio that results in SE membrane flexibility at different weight percents of binder 1. All compositions that fall within or below the formula result in flexible SE membranes.
[0071] For binder 2, the curve fit is given by the equation: Br / Cl=345x-1.94 (Formula II) where x is the weight percent of binder 2 in the SE membrane.
[0072] Equation II describes the highest Br / Cl ratio that results in SE membrane flexibility at different weight percentages of binder 2.
[0073] It has been clearly shown that the structure of the binder plays an important role in determining the flexibility of the SE membrane.
[0074] The solid electrolyte materials were prepared according to the process of Example 1. The solid electrolyte particles were mixed with the binder 2 PTFE to form a mixture, and then each of them was formed into a solid electrolyte membrane with a desired thickness by a calendaring method. The mass percentage of the binder ranged from 0.5 mass% to 7 mass% in the mixture. The flexibility of the membrane was summarized in Table 2.
[0075] [Table 2]
[0076] In one aspect of the present disclosure, the electrolyte membrane is a) of formula Li x M1 y M2 z P 1-p M3 p S 6-a-b-q O q Cl a Br b (Formula I), wherein 4 ≦ x ≦ 8, 0 ≦ y < 1, 0 ≦ z < 1, 0 ≦ p < 1, 0 ≦ q < 1, 0 < a ≦ 2, 0 ≦ b < 2, 0 < 6 - a - b - q < 6, 0 < 1 - p ≦ 1, 0 ≦ b / a ≦ 20, M1 is at least one element of Group 1 or Group 11 other than H or Li in the periodic table, M2 is at least one element of Group 2 in the periodic table, M3 is at least one element of Group 14 in the periodic table, a sulfide solid electrolyte having the formula, and b) a binder in a mass percentage range of 0.05% to 10% by mass in the flexible electrolyte membrane, and the electrolyte membrane has a bending strain (ε M ) of 0.1% or more, the bending strain is given by the formula: ε M = h / (2r) where h is the thickness of the membrane and r is the bending radius of the membrane achieved without damage to the membrane.
[0077] In a second aspect, b / a has a value below a threshold value determined by the formula.
[0078] In a third aspect according to the second aspect, the formula is b / a = 183x - 2.11 (Formula I) for an acrylate binder, where x denotes the mass percentage of the acrylate binder in the electrolyte membrane.
[0079] In a fourth aspect according to the second aspect, the formula is b / a = 345x - 1.94 (Formula II) for a PTFE binder, where x denotes the mass percentage of the PTFE binder in the electrolyte membrane.
[0080] In a fifth embodiment according to the first aspect, the electrolyte membrane has a lithium ion conductivity in the range of 0.05 to 20 mS / cm.
[0081] In a sixth embodiment according to the first aspect, the electrolyte membrane has a lithium ion conductivity of 0.05 mS / cm or more.
[0082] In a seventh embodiment according to the first aspect, the electrolyte membrane has a thickness in the range of 5 μm to 300 μm.
[0083] In an eighth embodiment according to the first aspect, the electrolyte membrane further comprises a nonwoven fabric or equivalent as an underlayer.
[0084] In a ninth embodiment according to the first aspect, formula I is: a) Li x P.S. 6-a-b Cl a Br b , where 4≦x≦8, 0 <a≦2、0≦b<2、0<6-a-b<6; b) Li x M1 y P.S. 6-a-b Cl a Br b , where 4≦x≦8, 0 <y<1、0<a≦2、0≦b<2、0<6-a-b<6; c) Li x M2 z P.S. 6-a-b Cl a Br b , where 4≦x≦8, 0 <z<1、0<a≦2、0≦b<2、0<6-a-b<6; d) Li x P 1-p M3 p S 6-a-b Cl a Br b , where 4≦x≦8, 0 <p<1、0<a≦2、0≦b<2、0<6-a-b<6、0<1-p<1; e) Li x P.S. 6-a-b-q O q Cl a Br b, where 4≦x≦8, 0 <q≦1、0<a≦2、0≦b<2、0<6-a-b-q<6; f) Li x M1 y P.S. 6-a-b-q O q Cl a Br b , where 4≦x≦8, 0 <y<1、0<q<1、0<a≦2、0≦b<2、0<6-a-b-q<6; g) Li x M2 z P.S. 6-a-b-q O q Cl a Br b , where 4≦x≦8, 0 <z<1、0≦q<1、0<a≦2、0≦b<2、0<6-a-b-q<6;および h) Li x P 1-p M3 p S 6-a-b-q O q Cl a Br b , where 4≦x≦8, 0 <p<1、0<q<1、0<a≦2、0≦b<2、0<6-a-b-q<6、0<1-p<1; is selected from the group consisting of:
[0085] In a tenth embodiment according to the first aspect, the total molar amount of Br and Cl is less than 2, ie a+b≦2.
[0086] In an eleventh embodiment according to the first aspect, the sulfide solid electrolyte is: Li 5.8 P.S. 4.7 O 0.1 Cl 1.2 , Li 5.9 P 0.9 Ge 0.1 S 4.8 Cl 1.2 , Li 5.7 Na 0.1 P.S. 4.8 Cl 1.2 , Li 5.4 P.S. 4.4 Cl 0.4 Br 1.2 , Li 5.8 P.S. 4.8 Cl 0.4 Br0.8 , Li 5.4 P.S. 4.4 Cl 0.6 Br 1.0 , Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 , Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 , Li 5.8 P.S. 4.8 Cl 0.6 Br 0.6 , Li 5.4 P.S. 4.4 Cl 1.0 Br 0.6 , Li 5.4 P.S. 4.4 Cl 1.2 Br 0.4 , Li 5.8 P.S. 4.8 Cl 0.8 Br 0.4 , Li 5.8 P.S. 4.8 Cl 1.0 Br 0.2 , and Li 5.4 P.S. 4.4 Cl 1.4 Br 0.2 The compound has a formula selected from the group consisting of:
[0087] In a twelfth aspect of the present disclosure, an all-solid-state battery comprises an electrolyte membrane as disclosed herein.
[0088] In a thirteenth embodiment of the present disclosure, the all-solid-state battery further comprises a positive electrode made from a positive electrode electroactive material.
[0089] In a fourteenth embodiment according to the thirteenth embodiment, the positive electrode electroactive material exhibits a redox reaction at a potential of 2 V or greater versus Li / Li+ during operation of the all-solid-state battery.
[0090] In a fifteenth embodiment of the present disclosure, a method for preparing an electrolyte membrane includes mixing particles of a sulfide solid electrolyte and a polymer binder to obtain a mixture.
[0091] In a sixteenth aspect according to the fifteenth aspect of the present disclosure, sulfide solid electrolyte particles are synthesized by mixing precursor powders in a stoichiometric ratio in an inert atmosphere, followed by sintering at 400-700° C. for 4-24 hours and grinding, the precursor powders including Li2S, Na2S, P2S5, LiCl, LiBr, Li2O, and GeS2.
[0092] In a seventeenth embodiment according to the fifteenth aspect of the present disclosure, the mixture comprises a solvent and the mixture is a slurry.
[0093] In an eighteenth embodiment according to the sixteenth aspect of the present disclosure, the method comprises: a) coating the mixture onto a substrate comprising a film and a nonwoven fabric, followed by vacuum drying at room temperature to obtain a dry coating bonded to the nonwoven fabric; and b) peeling the dry coating from the film, thereby obtaining an electrolyte membrane comprising the dry coating and the nonwoven fabric; Further includes:
[0094] In a nineteenth embodiment according to the eighteenth embodiment of the present disclosure, the film in the substrate is a PET film, and the nonwoven fabric is made of polyester having a thickness of about 10 μm.
[0095] In a twentieth embodiment according to the fifteenth embodiment of the present disclosure, the mixture is substantially free of solvent, and the mixture is formed into a membrane by a calendaring process.
Claims
1. In the electrolyte membrane, a) Formula Li x M1 y M2 z P 1-p M3 p S 6-a-b-q O q C a B b a sulfide solid electrolyte having the formula (I) in which 4≦x≦8, 0≦y<1, 0≦z<1, 0≦p<1, 0≦q<1, 0<a≦2, 0≦b<2, 0<6-a-b-q<6, 0<1-p≦1, 0≦b / a≦20, M1 is at least one element from Group 1 or Group 11 of the Periodic Table other than H or Li, M2 is at least one element from Group 2 of the Periodic Table, and M3 is at least one element from Group 14 of the Periodic Table; b) a weight percent of a binder in the electrolyte membrane ranging from 0.05% to 10% by weight; Including, The electrolyte membrane has a bending strain (ε M ) The bending strain is determined by the formula: ε M =h / (2r) where h is the thickness of the membrane and r is the bending radius of the membrane achieved without any observable damage to the membrane.
2. 2. The electrolyte membrane of claim 1, wherein b / a has a value less than or equal to a threshold value determined by the formula:
3. 3. The electrolyte membrane of claim 2, wherein the formula is b / a=183x-2.11 (Formula I) for an acrylate binder, where x refers to the weight percent of the acrylate binder in the electrolyte membrane.
4. 3. The electrolyte membrane of claim 2, wherein the formula is b / a=345x-1.94 (Formula II) for a PTFE binder, where x refers to the weight percent of the PTFE binder in the electrolyte membrane.
5. 10. The electrolyte membrane of claim 1, wherein the electrolyte membrane has a lithium ion conductivity in the range of 0.05 to 20 mS / cm.
6. 2. The electrolyte membrane of claim 1, wherein the electrolyte membrane has a lithium ion conductivity of 0.05 mS / cm or greater.
7. The electrolyte membrane of claim 1 , wherein the electrolyte membrane has a thickness in the range of 5 μm to 300 μm.
8. The electrolyte membrane according to claim 1 , further comprising a nonwoven fabric as an underlayer.
9. wherein said formula I is: a) Li x PS 6-a-b Cl a Br b , where 4≦x≦8, 0<a≦2, 0≦b<2, 0<6-a-b<6; b) Li x M1 y PS 6-a-b Cl a Br b , where 4≦x≦8, 0<y<1, 0<a≦2, 0≦b<2, 0<6-a-b<6; c) Li x M2 z PS 6-a-b Cl a Br b where 4 ≤ x ≤ 8, 0 < z < 1, 0 < a ≤ 2, 0 ≤ b < 2, 0 < 6 - a - b < 6; d) Li x P 1-p M3 p S 6-a-b Cl a Br b where 4 ≦ x ≦ 8, 0 < p < 1, 0 < a ≦ 2, 0 ≦ b < 2, 0 < 6 - a - b < 6, 0 < 1 - p < 1; e) Li x PS 6-a-b-q O q Cl a Br b , where 4≦x≦8, 0<q≦1, 0<a≦2, 0≦b<2, 0<6-a-b-q<6; f) Li x M1 y PS 6-a-b-q O q Cl a Br b where 4 ≤ x ≤ 8, 0 < y < 1, 0 < q < 1, 0 < a ≤ 2, 0 ≤ b < 2, 0 < 6 - a - b - q < 6; g) Li x M2 z P.S. 6-a-b-q O q C a B b , where 4≦x≦8, 0<z<1, 0≦q<1, 0<a≦2, 0≦b<2, 0<6−a−b−q<6; and h) Li x P 1-p M3 p S 6-a-b-q O q Cl a Br b , where 4 ≤ x ≤ 8, 0 < p < 1, 0 < q < 1, 0 < a ≤ 2, 0 ≤ b < 2, 0 < 6 - a - b - q < 6, 0 < 1 - p < 1; The electrolyte membrane of claim 1 , selected from the group consisting of:
10. 2. The electrolyte membrane according to claim 1, wherein a+b≦2.
11. The sulfide solid electrolyte is: Li 5.8 P.S. 4.7 O 0.1 C 1.2 , Li 5.9 P 0.9 Ge 0.1 S 4.8 C 1.2 , Li 5.7 Na 0.1 P.S. 4.8 C 1.2 , Li 5.4 P.S. 4.4 C 0.4 B 1.2 , Li 5.8 P.S. 4.8 C 0.4 B 0.8 , Li 5.4 P.S. 4.4 C 0.6 B 1.0 , Li 5.4 P.S. 4.4 C 0.8 B 0.8 , Li 5.4 P.S. 4.4 C 0.8 B 0.8 , Li 5.8 P.S. 4.8 C 0.6 B 0.6 , Li 5.4 P.S. 4.4 C 1.0 B 0.6 , Li 5.4 P.S. 4.4 C 1.2 B 0.4 , Li 5.8 P.S. 4.8 C 0.8 B 0.4 , Li 5.8 P.S. 4.8 C 1.0 B 0.2 , and Li 5.4 P.S. 4.4 C 1.4 B 0.2 2. The electrolyte membrane of claim 1 having a formula selected from the group consisting of:
12. An all-solid-state battery comprising the electrolyte membrane according to claim 1.
13. 13. The all-solid-state battery of claim 12, further comprising a positive electrode made from the positive electrode electroactive material.
14. 14. The all-solid-state battery of claim 13, wherein the positive electrode electroactive material exhibits a redox reaction at a potential of 2 V or greater versus Li / Li+ during operation of the all-solid-state battery.
15. 10. A method for preparing an electrolyte membrane according to claim 1, comprising the step of mixing particles of the sulfide solid electrolyte and a polymeric binder to obtain a mixture.
16. The sulfide solid electrolyte particles are synthesized by mixing precursor powders in a stoichiometric ratio in an inert atmosphere, followed by sintering at 400-700° C. for 4-24 hours and grinding, the precursor powders being Li 2 S, Na 2 S, P 2 S 5 , LiCl, LiBr, Li 2 O, GeS 2 16. The method of claim 15, wherein said compound is selected from the group consisting of:
17. 16. The method of claim 15, wherein the mixture includes a solvent and the mixture is a slurry.
18. a) coating the mixture onto a substrate comprising a film and a nonwoven fabric, followed by vacuum drying at room temperature to obtain a dry coating bonded to the nonwoven fabric; and b) peeling the dry coating from the film, thereby obtaining an electrolyte membrane comprising the dry coating and the nonwoven fabric; 20. The method of claim 17, further comprising:
19. 20. The method of claim 18, wherein the film in the substrate is a PET film and the nonwoven fabric is made of polyester having a thickness of about 10 μm.
20. 16. The method of claim 15, wherein the mixture is substantially free of solvent and the mixture is formed into a membrane by calendering.
Citation Information
Patent Citations
Solid electrolyte sheet and all-solid type secondary battery
JP2016031789A
Sulfide solid electrolyte
WO2018047566A1
Solid ion conductor compound, solid electrolyte comprising same, electrochemical cell comprising same, and manufacturing method thereof
WO2022071644A1
Composite membrane comprising solid electrolyte, method of making said composite membrane, and electrochemical cell comprising said composite membrane
US11024876B2
Lithium argyrodite
US8075865B2